PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH PADA PEMERINTAH KABUPATEN MUSI RAWAS UTARA - Miki Indika (Jurnal Akuntansi, 2020)
This study aims to see whether the government internal control system partially influences the effectiveness of regional financial management, whether human resources partially influence the effectiveness of regional financial management, and simultaneously government internal control system and human resource competencies influence the effectiveness of regional financial management. This study aims to examine the effect of the government's internal control system and human resource competence on the effectiveness of regional financial management. There are three variables in this study, namely the government internal control system, human resource competency, and the effectiveness of regional financial management which entirely developed into 15 indicators. The sampling technique used is purposive sampling with a population of 12 (twelve) Regional Apparatus Organizations that implement the Government's Internal Control System where each Regional Device Organization is taken as many as twelve respondents. The data collection techniques are questionnaires and observations. The data analysis method used in the study is a multiple regression analysis with the help of SPSS version 20. The result indicates that Government internal control system partially had a significant effect on the effectiveness of regional financial management, the human resource competencies partially had a significant effect on the effectiveness of regional financial management